1992
DOI: 10.1530/jrf.0.0960865
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of pulsatile luteinizing hormone secretion by gonadotrophin-releasing hormone antagonist does not affect episodic progesterone secretion or corpus luteum function in ewes

Abstract: Progesterone secretion has been observed to be episodic in the late luteal phase of the oestrous cycle of ewes and is apparently independent of luteinizing hormone (LH). This study investigated the effects of suppressing the pulsatile release of LH in the early or late luteal phase on the episodic secretion of progesterone. Six Scottish Blackface ewes were treated i.m. with 1 mg kg-1 body weight of a potent gonadotrophin-releasing hormone (GnRH) antagonist on either day 4 or day 11 of the luteal phase. Six ewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…It seems clear that the LH surge is essential for ovulation and luteinization of the ovulated follicular cells into the luteal cells, however, the role for LH pulses, after the LH surge, is still controversial. Consistent with our results, other researchers have also found that treatment with a GnRH antagonist eliminated pulsatile LH secretion but had little or no effect on circulating P4 and CL function (Baird, 1992;McNeilly et al, 1992). In contrast, when sheep are hypophysectomized on day 5 after estrus and CL recovered on day 12, circulating P4, luteal P4, and weight of CL are lower than expected for a day 12 CL but similar to a day 5 CL (Kaltenbach et al, 1968; Denamur et al, 1973;Farin et al, 1990).…”
Section: Factors Regulating Circulating P4 Concentrationssupporting
confidence: 92%
“…It seems clear that the LH surge is essential for ovulation and luteinization of the ovulated follicular cells into the luteal cells, however, the role for LH pulses, after the LH surge, is still controversial. Consistent with our results, other researchers have also found that treatment with a GnRH antagonist eliminated pulsatile LH secretion but had little or no effect on circulating P4 and CL function (Baird, 1992;McNeilly et al, 1992). In contrast, when sheep are hypophysectomized on day 5 after estrus and CL recovered on day 12, circulating P4, luteal P4, and weight of CL are lower than expected for a day 12 CL but similar to a day 5 CL (Kaltenbach et al, 1968; Denamur et al, 1973;Farin et al, 1990).…”
Section: Factors Regulating Circulating P4 Concentrationssupporting
confidence: 92%
“…However, the effect on secretion of progesterone is not as dramatic as that observed in primates, and treatment of cows with a GnRH antagonist after the corpus luteum is fully developed had no effect on secretion of progesterone (283). Treatment of sheep during development or maintenance of the corpus luteum with GnRH antagonist had very little effect on the secretion of progesterone (225). Thus pulsatile release of LH appears necessary for normal luteal function in primates and for luteal development in cows.…”
Section: Requirements For Pulsatile Release Of Lh For Normal Luteamentioning
confidence: 95%
“…The limit of detection was 0.2 pg/ml and intra-and interassay CV were !12%. Progesterone was measured by RIA without extraction as described previously (McNeilly et al 1992). The limit of detection was 0.2 pg/ml and intra-and interassay CV were !11%.…”
Section: Hormone Assaysmentioning
confidence: 99%